Analisis Penerapan Sistem Informasi Akuntansi pada PT Z Berdasarkan Teori dan Praktik Lapangan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study focuses on evaluating the implementation of the accounting information system at PT Z, covering the credit purchasing system, credit sales, physical inventory counting, payroll, and fixed asset acquisition. The method used is descriptive qualitative through direct observation and interviews. The result of the study indicate that the accounting system at PT Z has been operating quite effectively in line with operational needs, although it does not fully align with he theory proposed by Mulyadi. Several discrepancies were found, including the absence of a general journal (memorial book) in certain recordings and a lack of separation of duties between recordkeeping and physical supervision, which could potentially weaken internal control. On the other hand, the company has utilized a technology-based system for recording aand physical supervision, which suports efficiency and accuracy. This study recommends improvements in documentation, procedures, internal controls, human resource training, and broader application of information technology. Periodic evaluations are also important to ensure that the accounting system remains in line with bussiness needs and regulatory developments. The company’s name is withheld in this report to maintain research ethics and confidentiality.